2014
DOI: 10.1007/s13197-014-1370-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of stable flaxseed oil emulsions as a potential delivery system of ω-3 fatty acids

Abstract: The objective of the present study was to develop a stable flaxseed oil emulsion for the delivery of omega-3 (ω-3) fatty acids through food fortification. Oil-in-water emulsions containing 12.5 % flaxseed oil, 10 % lactose and whey protein concentrate (WPC)-80 ranging from 5 to 12.5 % were prepared at 1,500, 3,000 and 4,500 psi homogenization pressure. Flaxseed oil emulsions were studied for its physical stability, oxidative stability (peroxide value), particle size distribution, zeta (ζ)-potential and rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 46 publications
11
48
0
Order By: Relevance
“…The results agree with the observations reported by Goyal et al. () and Kunh and Cunha (2012) for flaxseed oil emulsion stabilized using different emulsifiers. Kunh and Cunha (2012) observed particle sizes as low as 460 nm when the pressure was increased to 80 MPa with 4 number of passes.…”
Section: Resultssupporting
confidence: 92%
“…The results agree with the observations reported by Goyal et al. () and Kunh and Cunha (2012) for flaxseed oil emulsion stabilized using different emulsifiers. Kunh and Cunha (2012) observed particle sizes as low as 460 nm when the pressure was increased to 80 MPa with 4 number of passes.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, higher intakes of ω-6 fatty acids (in the form of refined vegetable oils such as soybean, sunflower, safflower, cottonseed and groundnut oil) in regular diet leads to the imbalance of ω-6 to ω-3 ratio in human body. It has been reported that ω-6:ω-3 ratio in current Indian urban, Indian rural and Western diet is 38-50:1, 5-6:1 and 16:1, respectively (3,4), over the recommended ratio of 5:1 (5).…”
Section: Effect Of Microencapsulation and Spray Drying On Oxidative Smentioning
confidence: 99%
“…Goyal et al (2015) produced microcapsules with a high content of flaxseed oil (over 35% w/w, on a dry basis) using milk protein/ lactose (1:1). They concluded that the developed flaxseed oil powder was stable throughout the storage of 6 months, and its peroxide value remained below the maximum permissible limit (≤5 meq per kg oil) stipulated in Codex Alimentarius Commission.…”
Section: Free Oil Content Microencapsulation Efficiency and Oxidatimentioning
confidence: 99%